‘Where is the Promise of his Coming?’ The Complaint of the Scoffers in 2 Peter 3.4 - Adams, Edward (New Testament studies, 2005)
A close analysis of the report of 2 Pet 3.4, paying attention to its precise wording, and a careful reading of the author's response to it in the verses that follow show that the prevailing interpretation of the scoffers' eschatological mockery is unsound. The target of the scoffers' criticism was not so much the parousia of Jesus as the OT promise of a final, eschatological irruption underlying it. Their scepticism was founded neither on the failure of Jesus to come back within a generation, nor on a denial of divine intervention. Rather, it was based on the long period of time that had elapsed since the promise was originally made and the assumption that the eschatological promise involved the prospect of cosmic destruction, which the scoffers rejected on philosophical grounds.